2017
DOI: 10.3390/ijms18112412
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Crataegus oxyacantha and Rosmarinus officinalis Attenuate Ischemic Myocardial Damage by Decreasing Oxidative Stress and Regulating the Production of Cardiac Vasoactive Agents

Abstract: Numerous studies have supported a role for oxidative stress in the development of ischemic damage and endothelial dysfunction. Crataegus oxyacantha (Co) and Rosmarinus officinalis (Ro) extracts are polyphenolic-rich compounds that have proven to be efficient in the treatment of cardiovascular diseases. We studied the effect of extracts from Co and Ro on the myocardial damage associated with the oxidative status and to the production of different vasoactive agents. Rats were assigned to the following groups: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 63 publications
(76 reference statements)
0
11
0
2
Order By: Relevance
“…Thanks to its high antioxidant's potential and anti-inflammatory effects, CO herbal formulation is currently available and known for its documented effect to prevent or ameliorate the consequences of numerous oxidative stress-related disorders [18,19,21]. Previous investigations have demonstrated that different CO extractions have anti-inflammatory, anti-oxidative stress, and protective effects against tissue damage promoted in animals in association with ischemia-reperfusion [22] and scopolamine [23] in brain, ischemia-reperfusion in heart [24,25], hypercholesterolemia [26], and in high fat food plan [27] in liver. The hepatoprotective effects of standardized extract of HAW was evaluated against acute liver injury induced by CCL4 and hypocholesterolemic agent [26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its high antioxidant's potential and anti-inflammatory effects, CO herbal formulation is currently available and known for its documented effect to prevent or ameliorate the consequences of numerous oxidative stress-related disorders [18,19,21]. Previous investigations have demonstrated that different CO extractions have anti-inflammatory, anti-oxidative stress, and protective effects against tissue damage promoted in animals in association with ischemia-reperfusion [22] and scopolamine [23] in brain, ischemia-reperfusion in heart [24,25], hypercholesterolemia [26], and in high fat food plan [27] in liver. The hepatoprotective effects of standardized extract of HAW was evaluated against acute liver injury induced by CCL4 and hypocholesterolemic agent [26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that extracts of C. laevigata are beneficial as an antioxidant, (Cuevas-Durán et al, 2017;Kirakosyan et al, 2003). The antioxidant properties of C. laevigata are due to the high total content of phenols (Ferioli et al, 2020), but also to proanthocyanidins, flavones and flavonols (Škerget et al, 2005).…”
Section: Pharmaceutical Usesmentioning
confidence: 99%
“…In a study, UV/MS analysis coupled with 1D/2D nuclear magnetic resonance (NMR) spectroscopy was used to detect the compounds extracted from the ethyl acetate extract of C. oxyacantha, which included naringenin, epicatechin, quercetin-3-O-β-glucoside, and quercetin [28]. The presence of rutin and quercetin obtained from C. oxyacantha extracts using HPLC was also reported [29]. The work of Nabavi et al focused on the polyphenolic composition of C. monogyna Polyphenol compounds from C. oxyacantha extracts, including epicatechin, epicatechin gallate (ECG), rutin, caffeic, and caftaric acids, were identified using HPLC-DAD and LC-MS/MS techniques [27].…”
Section: Phytochemical Composition Of Hawthornmentioning
confidence: 99%